1998
DOI: 10.1038/sj.ejhg.5200164
|View full text |Cite
|
Sign up to set email alerts
|

Evidence against a major role of PEG1/MEST in Silver–Russell syndrome

Abstract: Silver-Russell syndrome (SRS) is a heterogeneous disorder characterised by interauterine and postnatal growth retardation, with or without additional dysmorphic features. Most cases are sporadic but a few familial cases have been described. A subset of patients exhibit maternal uniparental disomy for chromosome 7 (mUPD7) strongly suggesting that genomic imprinting plays a role in the aetiology of the disease. We and others have recently characterised the human PEG1/MEST gene, the first imprinted gene known to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 24 publications
2
29
0
2
Order By: Relevance
“…In mice, mutation of the paternal allele of Peg1 (Mest) resulted in fetal growth retardation and was considered a candidate for SRS (24). However, a recent analysis has suggested that PEG1 has no role in SRS (33). Therefore, Sgce is another candidate for this condition.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, mutation of the paternal allele of Peg1 (Mest) resulted in fetal growth retardation and was considered a candidate for SRS (24). However, a recent analysis has suggested that PEG1 has no role in SRS (33). Therefore, Sgce is another candidate for this condition.…”
Section: Discussionmentioning
confidence: 99%
“…However, mutational screening of SRS patients for PEG1/MEST [48] and GRB10 [49] has not clearly proved their involvement in the etiology of the syndrome.…”
Section: Chromosomementioning
confidence: 99%
“…Two potential candidate genes for SRS on chromosome 7 (MEST and EGFR) were characterized and tested, but so far none of these have been shown to harbor mutations in SRS patients [Riesewijk et al, 1998;Wakeling et al, 1998b]. The identification and functional characterization of the growth-related gene(s) on chromosome 7 and other human chromosomes known to undergo differential imprinting might ultimately dissect the distinct contribution of maternal and paternal transcripts to the control of intrauterine and postnatal growth.…”
Section: Silver-russell Syndrome and Cystic Fibrosis Associated With mentioning
confidence: 98%